Thirteen-year analyses of medical oncology outpatient day clinic data: a changing field. Issue 5 (13th October 2020) - Marhold, Maximilian; Topakian, Thais; Agis, Hermine; Bartsch, Rupert; Berghoff, Anna S; Brodowicz, Thomas; Fuereder, Thorsten; Ilhan-Mutlu, Aysegül; Kiesewetter, Barbara; Krainer, Michael; Locker, Gottfried J; Marosi, Christine; et al.
Abstract : Background: Novel treatment modalities like targeted therapy and immunotherapy are currently changing treatment strategies and protocols in the field of medical oncology. Methods: Numbers of patients and patient contacts admitted to medical oncology day clinics of a large European academic cancer centre in the period from 2006 to 2018 were analysed using our patient administration system. Results: A patient cohort of 9.870 consecutive individual patients with 125.679 patient contacts was descriptively and retrospectively characterised. Mean age was 59.9 years. A substantial increase in both individual patients treated per year (+45.4%; 2006: 1.100; 2018: 1.599) and annual patient contacts (+63.3%; 2006: 8.857; 2018: 14.467) between 2006 and 2018 was detected. Hence and most interestingly, the ratio of visits per patient increased by approximately one visit per patient per year over the last 12 years (+12.4%; 2006: 8.0; 2018: 9.0). Further, a decrease of patient contacts in more prevalent entities like breast cancer was found, while contacts for orphan diseases like myeloma and sarcoma increased substantially. Interestingly, female patients showed more per patient contacts as compared with men (13.5 vs 11.9). Lastly, short-term safety data of outpatient day clinic admissions are reported. Conclusions: We present a representative and large set of patient contacts over time that indicates an increasing load in routine clinical work of outpatient cancer care. Increases observed were highest for orphan diseases, likely attributed to centralisation effects and increased treatment complexity.